Adventure Destinations In Indonesia: The Function Of Perceived Value, And Effect On Visitor Experience And Revisit Intention - Mahmudi Rosid, Moch. (Publisher Cv. Inara, 2024)
Management of the Mt. Penanggungan destination which has not been managed well. Can management science contribute to the Mt. Penanggungan adventure tourism destination? This research examines marketing management in adventure tourism destinations, which is usually synonymous with customer loyalty, and the determinant is always